Produção de hidromel utilizando reatores de células livres - Santos, Jonnatas Evaristo dos (2024)
Beekeeping, practiced globally, is influenced by variations in bee species, climate and economic development. The integration of traditional and modern methods is essential to improve the production of honey, which has around 200 components, including carbohydrates, nutrients and natural antioxidants. The quality of honey depends on its botanical origin, color, aroma and chemical composition, which also influences the production of mead, a fermented drink made from honey. Mead, one of the oldest alcoholic drinks, is an attractive alternative to diversify beekeeping products, especially in regions with beekeeping potential, such as Catolé do Rocha-PB. The production of mead in free-cell reactors, which can be optimized by varying parameters such as honey concentration, temperature and nitrogen source, offers a valuable opportunity to add value to the production chain, stimulate the development of micro-enterprises and generate jobs. Research has shown that manipulating these parameters can improve ethanol production and mead quality, making it an economically viable option for beekeepers. The 23 factorial experimental design methodology + star configuration (Rotational Central Compound Design-DCCR) was used to verify the influences of the input variables: initial sugars (°Brix); temperature and nitrogen source (N) on the answer: ratio of ethanol produced in the mead production fermentation to initial sugars (E/B). It was verified, with the results, that with an increase in the nitrogen source and with a temperature above 24 °C, with a sugar concentration in the honey, at 17.5 °Brix, maximum values of the E/B ratio are obtained, or that is, greater ethanol production in the fermentation process. It was observed that the preparation of mead with honey (MIEL-O) from the region of Catolé do Rocha, PB, identified as marmeleiro flower honey, is technically viable based on the process of fermentative kinetics with free cells, only requiring a small pH correction, as the other parameters remained within the identity standards expected to produce the drink on a commercial scale.